Phosphorus Forms in the Indus River Alluvial and Loess, Shale and Limestone Derived Residual Soils - Memon1, Mehrunisa; Saleem Akhtar2, Mohammad; Suleman Memon1, Kazi; Stüben3, Doris (Asian Journal of Chemistry, 2011)
Phosphorus (P) fractionation helps to understand the soil processes related to its agronomic efficiency and contribution to environmental quality. Distribution of P in various forms in the slightly weathered calcareous soils of the Indus plain (Pakistan) has not been investigated which limits understanding of long-term P chemistry trends. Several alluvial and residual soils were sampled at genetic horizon depths and the soil inorganic P forms were sequentially extracted by the Jiang and Gu scheme along with their mineral and chemical parameters. Two highly weathered soils from Germany were included for comparison. Apatite was 500-600 mg kg-1 in the alluvial soils, 200-300 mg kg-1 in the loess and shale derived soils and a major contributor to total P. With strong loss of apatite from the surface, the highly weathered soils had almost equal contribution to total from the pools: (a) P desorbed from and released by iron oxide dissolution, (b) occurring as apatite and (c) occurring as organic-P. The dicalcium phosphate and octacalcium phosphate accumulated in surface horizon of the fertilized alluvial soils and below 75 cm in strongly structured silty clay and massive loamy sand soils. NaOH-Na2CO3 appeared to be an ineffective treatment for desorbing P from the well crystallized goethite found in the alluvial soils. CBD and extractable iron (Fed), oxalate extractable iron (Feo) and aluminum (Alo), goethite (Gt), dissolved organic carbon (DOC), CaCO3 and clay kaolinite explained 75-99 % of variability in the soil P forms. This study demonstrates role of soil parent material, weathering and land use in distribution of soil P forms and their relationships to soil-test P.